Experimental and Computational Investigation of Transport Phenomena in Initiated Chemical Vapor Deposition (icvd) Process - Ateş, Selcan; Ebil, Özgenç; Ebil, Özgenç (Izmir Institute of Technology, 2017)
As a polymer thin-film deposition technique, initiated CVD (iCVD) is a heterogeneous process involving gas phase precursors and solid film formation on a solid/liquid substrates at different temperature regions. Obtaining fine-tuned film properties over different substrate geometries at different process conditions is a challenging tasks and requires experimental trials. The major goal of this study is to develop a computational model which describes all relevant transport phenomena occurring in iCVD process, and which is capable to predict the polymer film thickness at different deposition conditions for flat and/or non-flat substrates in a 3D reactor geometry. A Finite Element Analysis (FEA)-based 3D computational model, which can be applied to a variety number of iCVD reactor and substrate geometries, has been developed in the study. To validate the model, reported experimental conditions of 1H,1H,2H,2Hperfluorodecyl acrylate (PFDA) deposition with t-butyl peroxide (TBPO) initiator, and butyl acrylate (BA) deposition with t-amyl peroxide (TAPO) initiator, are applied to the model, respectively. The simulation results of both deposition processes show good agreement with experimental results reported in literature. Presented model successfully describes the relevant transport phenomena, and provides a priori predictions on polymerization rate, and film thickness on complex substrate geometries for a polymerization reaction with known kinetic data. For further studies, presented model can be modified or used as an approach for modeling of other types of CVD systems as well as facilitating process scale-up. The model can also extract valuable polymerization kinetics data provided that a sufficient number of experiments are performed at a specified substrate temperature, and process parameters and measured final film thicknesses are entered to the model.
Başlatılmış Kimyasal Buhar Biriktirme Prosesinde Taşınım İşlemlerinin Deneysel ve Hesaplamalı İncelenmesi
Thesis (Doctoral)--Izmir Institute of Technology, Chemical Engineering, Izmir, 2017
Full text release delayed at author's request until 2021.01.17
Includes bibliographical references (leaves: 84-86)
Text in English; Abstract: Turkish and English
Keywords: iCVD; Perfluorodecyl acrylate; Thin films; Polymerization; Computer aided modelling; Chemical vapor deposition